(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Inflammatory diseases of the teeth and jaws still occupies the main place among other dental diseases. Among children with acute odontogenic inflammatory processes of the maxillofacial region, a significant proportion are patients with periostitis. There is no consensus in the literature regarding the frequency of the disease depending on age and causative teeth. This article presents the results of studying the role of individual teeth in the development of acute purulent periostitis of the jaws in children.